2005
DOI: 10.1111/j.1467-789x.2005.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in Iran

Abstract: Recent descriptive studies suggest that Iran has geared in the nutrition and epidemiological transition processes. Therefore, while the problems of undernutrition (e.g. growth retardation and micronutrient deficiencies) still exist, the burden of overweight/obesity and diet-related chronic diseases is increasing. The prevalence of overweight (body mass index > or = 85th reference percentiles) among urban 15-39 and 40-69 year olds is estimated at about 22% and 40% respectively. Corresponding values in rural are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 3 publications
2
44
0
Order By: Relevance
“…A recent review indicated that the prevalence of overweight (BMI $ 85th reference percentiles) among the urban 15-39 and 40-69-year-olds was 22% and 40%, respectively. Corresponding values in rural areas were 16% and 26%, respectively 23 . On the other hand, a study in Tehran showed much higher prevalence rates of generalised and abdominal obesity; 67% of women and 29% of the men were obese, and abdominal obesity was detected in 93% of the women and 74.1% of the men 24 .…”
mentioning
confidence: 96%
“…A recent review indicated that the prevalence of overweight (BMI $ 85th reference percentiles) among the urban 15-39 and 40-69-year-olds was 22% and 40%, respectively. Corresponding values in rural areas were 16% and 26%, respectively 23 . On the other hand, a study in Tehran showed much higher prevalence rates of generalised and abdominal obesity; 67% of women and 29% of the men were obese, and abdominal obesity was detected in 93% of the women and 74.1% of the men 24 .…”
mentioning
confidence: 96%
“…The increase in type 2 diabetes in the U.S. population reflects the trend in obesity (4). Obesity rates in the European countries are somewhat lower (10% to 30%) than those in the U.S. population, but an obesity prevalence of 15% to 30% has been reported even in developing countries, such as Uruguay, Iran, and Morocco (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The significant prevalence of overweight in Iran [12][13][14] necessitates studying different aspects of dietary habits, especially among adolescents. Appropriate public measures can then be designed according to any deviations from optimal eating practices.…”
Section: Introductionmentioning
confidence: 99%